Endogenous feline leukemia virus long terminal repeat integration site diversity is highly variable in related and unrelated domestic cats - Elliott S. Chiu; Coby A. McDonald; Roderick B. Gagne; Henry Dunkleberger; Matthew Moxcey; Sue VandeWoude (Retrovirology, 2024)
Abstract Endogenous retroviruses (ERV) are indicators of vertebrate evolutionary history and play important roles as homeostatic regulators. ERV long terminal repeat (LTR) elements may act as cis-activating promoters or trans-activating enhancer elements modifying gene transcription distant from LTR insertion sites. We previously documented that endogenous feline leukemia virus (FeLV)-LTR copy number variation in individual cats tracks inversely with susceptibility to virulent FeLV disease. To evaluate FeLV-LTR insertion characteristics, we assessed enFeLV-LTR integration site diversity in 20 cats from three genetically distinct populations using a baited linker-mediated PCR approach. We documented 765 individual integration sites unequally represented among individuals. Only three LTR integration sites were shared among all individuals, while 412 sites were unique to a single individual. When primary fibroblast cultures were challenged with exogenous FeLV, we found significantly increased expression of both exogenous and endogenous FeLV orthologs, supporting previous findings of potential exFeLV-enFeLV interactions; however, viral challenge did not elicit transcriptional changes in genes associated with the vast majority of integration sites. This study assesses FeLV-LTR integration sites in individual animals, providing unique transposome genotypes. Further, we document substantial individual variation in LTR integration site locations, even in a highly inbred population, and provide a framework for understanding potential endogenous retroviral element position influence on host gene transcription.